PENGARUH TINGKAT SUKU BUNGA DEPOSITO, KURS VALUTA ASING DAN TINGKAT INFLASI TERHADAP VOLUME PERDAGANGAN SAHAM PADA BURSA EFEK INDONESIA - Situmeang, Susi E.; Munthe, Kornel; Purba, Antonius M (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine the effect of deposit interest rates, foreign exchange rates and inflation rates on the volume of stock trading on the Indonesia Stock Exchange. This study applies a survey method to 54 Manufacturing companies that have been listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used the proportional random sampling method. The research data were analyzed using multiple linear regression analysis. The results showed that the variable deposit interest rate, foreign exchange rate, inflation rate simultaneously had a significant effect on stock trading volume and the variable deposit interest rate, foreign exchange rate, inflation rate partially had a positive and significant effect on the volume of stock trading in manufacturing companies in Indonesia. Indonesia stock exchange. The coefficient of determination (R^2) is 50.7 percent, this shows that variations in the variable deposit interest rate, foreign exchange rate, inflation rate can explain the variation in stock trading volume 50.7%.